Analisis Perputaran Modal Kerja Pada Pt Hanjaya Mandala Sampoerna,Tbk - Yuliana, Yuliana (Jurnal Ekonomi STIEP ( JES ), 2019)
Working capital is excess current assets againts short-term debt. This excess is called net working capital.The problem studied in this study is how much the working capital needs of PT Hanjaya Mandala Sampoerna, Tbkby using the working capital turnover formula.The conclusion of this study is that working capital is described using ratios Working Capital Turnoverwhich measures working capital turnover where the sale proceeds divided by working capital. Working capitalturnover in 2015 amounted to 9,89 % in 2016 amounted to 5,49 %, whereas in 2017 it was equal 2,05 % this showsthat there is an excess of working capital due to low receivables.Total corporate receivables in 2015 were lower than in 2016 and 2017 thus resulting in greater numberof attachments to the company’s working capital and faster working capital turnover.